Abdulla Aripov's Individual Interpretation Of The Issue Of Translation And Translation In His Publicistic Work (Texas Journal of Philology, Culture and History, 2025)
This article analyzes and studies the opinions and practical suggestions expressed in the journalism of the Hero of Uzbekistan, People's Poet Abdulla Oripov about the literary process, in particular, translation problems